Ontario’s Small Jewish Communities. ONTARIO JEWISH ARCHIVES. VIRTUAL EXHIBITION - Cohen, Leah (Archivaria, 2011)
Ontario’s Small Jewish Communities. ONTARIO JEWISH ARCHIVES. Virtual Exhibition http://www.ontariojewisharchives.org/exhibits/osjc/